Astragalus injection ameliorates lipopolysaccharide-induced cognitive decline via relieving acute neuroinflammation and BBB damage and upregulating the BDNF-CREB pathway in mice. (31st December 2022) - Liu, Ke; Wan, Guoran; Jiang, Ruhong; Zou, Li; Wan, Dong; Zhu, Huifeng; Feng, Shan
Abstract: Context: Post-sepsis cognitive impairment is one of the major sequelae observed in survivors of sepsis. Astragalus injection is the normally preferred treatment in sepsis in clinical settings. Objective: This study evaluated the benefits and related mechanism of Astragalus injection on post-sepsis cognitive impairment. Materials and methods: C57BL/6J mice were divided into three groups: Control, LPS (2.5 mg/kg, i.p.), and LPS + Astragalus injection (5.0 mL/kg). The surviving mice from sepsis were injected with material named Astragalus injection continuously for 13 days. Behavioural tests were first conducted to evaluate the benefits. Second, inflammatory cytokines secretion, BBB integrity, neurodegeneration, and protein expression was evaluated in vivo and in vitro . Results: Compared with the LPS group, mice in Astragalus injection group exhibited shorter escape latency (34.6 s versus 24.5 s) in the Morris water maze test. Treatment with Astragalus injection could reverse LPS-induced neuroinflammation in mice and BV2 cells. Continuous Astragalus injection treatment not only prevented blood–brain barrier dysfunction, but also prevented neurodegeneration. Further molecular docking tests and western blot results reflected that the main constituents of Astragalus injection could interact with TrkB (the estimated binding energy values were −7.0 to −5.0 kcal/mol) and upregulate the protein expression of BDNF/TrkB/CREB signalling pathway during the chronic stage in mice. Discussion: Astragalus injection treatment could reduce neuroinflammation, reverse BBB dysfunction, prevent neurodegeneration, and upregulate BDNF-CREB pathway during LPS-induced sepsis, ultimately preventing the development of cognitive decline. Conclusion: Astragalus injection could be a potential preventive and therapeutic strategy for sepsis survivors in clinical settings.